2020
DOI: 10.1149/1945-7111/ab9961
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Cathodic Thermal Behavior of Molten CaCl2 and Its Hygroscopic Chloride Mixture During Electrolysis

Abstract: A liquid metal electrochemically deposited in CaCl2 or its chloride melts serves as an effective reductant for active metal oxides. Although a very low oxygen concentration can be achieved at a considerably high electrolysis efficiency, the existence of small amount of water impurity in molten chlorides, which is very difficult to detect, causes low electrolysis efficiency. In this study, to clarify the morphological and thermal characteristics of a cathodic electrode in a slightly hygroscopic LiCl-KCl-CaCl2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…The morphological and thermal characteristics of a cathode in a slightly hygroscopic LiCl KClCaCl 2 melt were examined using a high-speed camera. 35) The measured heat absorption was considerably smaller than the thermodynamically predicted value, which suggested that the generated hydrogen formed a hydride by reacting with the liquid Ca that was electrodeposited on the cathode surface.…”
Section: Optimization Of Os Process Parametersmentioning
confidence: 82%
“…The morphological and thermal characteristics of a cathode in a slightly hygroscopic LiCl KClCaCl 2 melt were examined using a high-speed camera. 35) The measured heat absorption was considerably smaller than the thermodynamically predicted value, which suggested that the generated hydrogen formed a hydride by reacting with the liquid Ca that was electrodeposited on the cathode surface.…”
Section: Optimization Of Os Process Parametersmentioning
confidence: 82%
“…29 Moreover, CaCl 2 is also known to possess hygroscopic characteristic, enabling the evolution of hydrogen. 30,31 Therefore, KCl and CaCl 2 were separately added into LiCl molten electrolyte and the reduction of NiO in such electrolytes was studied.…”
Section: Influence Of the Electrolyte Composition On The Reduction Of...mentioning
confidence: 99%
“…After that, the cathodic potential remains relatively stable at around −0.52 V vs. Mo-QRE, which is the smallest value in the stage I, in comparison with other electrolytes. In fact, the hygroscopic nature of CaCl 2 31 and its hydrolysis in the presence of H 2 O could support the formation of protons in the electrolyte. At the same time, the addition of 30 wt% CaCl 2 not only lowered the liquidus temperature, 35 elevating the superheat of the melt at 110 °C, but also could result in an accelerated hydrolysis reaction and enhancing the activity of generated H + , thus the cathodic hydrogen evolution reaction.…”
Section: Influence Of the Electrolyte Composition On The Reduction Of...mentioning
confidence: 99%